(untitled) (Research, Society and Development, 2023)
One of the phases of processing cotton seeds for planting is their delinting, which consists of removing the linter to facilitate their distribution in the planting furrow and eventually eliminate pests and diseases. There are three types of delinting: mechanical, chemical and flame. The mechanical method is inefficient in extracting linter, the chemical method uses acid that is difficult to handle and is not accepted in organic or ecological systems, so the flame method is the most suitable for this type of agriculture. The objective of this work was to evaluate a fame delintator of simple design (prototype), low cost, efficient and suitable for small areas of agroecological cotton planting. Seeds were analyzed with linter, delinted with sulfuric acid and flamed with one, two and three passes through the prototype chamber. It was observed that there was no significant difference between the seeds with cotton linter (control) and the other treatments studied. This fact can be justified, due to the efficient artificial cooling adapted in the lower part of the equipment where the flamed seeds fall by gravity.